Holland and the Canadians, with 150 photographs - Phillips, Norman; Nikerk, J. (Amsterdam : Contact Publishing Company, 1946)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; Nederland; Canada